Longer Residence in the United States is Associated With More Physical Function Limitations in African Immigrant Older Adults. (February 2022) - Nkimbeng, Manka; Commodore-Mensah, Yvonne; Angel, Jacqueline L.; Bandeen-Roche, Karen; Thorpe, Roland J.; Han, Hae-Ra; Winch, Peter J.; Szanton, Sarah L.
Acculturation and racial discrimination have been independently associated with physical function limitations in immigrant and United States (U.S.)-born populations. This study examined the relationships among acculturation, racial discrimination, and physical function limitations in N = 165 African immigrant older adults using multiple linear regression. The mean age was 62 years ( SD = 8 years), and 61% were female. Older adults who resided in the United States for 10 years or more had more physical function limitations compared with those who resided here for less than 10 years ( b = −2.62, 95% confidence interval [CI] = [–5.01, –0.23]). Compared to lower discrimination, those with high discrimination had more physical function limitations ( b = −2.51, 95% CI = [–4.91, –0.17]), but this was no longer significant after controlling for length of residence and acculturation strategy. Residing in the United States for more than 10 years is associated with poorer physical function. Longitudinal studies with large, diverse samples of African immigrants are needed to confirm these associations.